Analysis of Community Satisfaction in Using Trans Banjarbakula Bus Transportation - Akhmad, Beni; Sari, Mita; Norkhadiza, Norkhadiza; Fitriani, Fitriani; Sintaman, Putri Irianti (Anterior Jurnal, 2024)
Trans Banjarbakula bus, this research aimed to find out how is the representation of community satisfaction in using trans Banjarbakula bus transportation in South Kalimantan Province. Methodology used in this research is descriptive quantitative. Data collection technique used in this research are observation, questionnaire and documentation with 100 passengers of trans Banjarbakula bus as respondents. Analysis of passenger’ satisfactions in Gambut Barakat Terminal bring in customer satisfaction index (CSI), overall dimensions servqual is about 90.28% which mean the passengers are satistified. Result of this research shows the CSI value based on 5 dimensions which are reliability 90,75%, responsiveness 88,50%, guarantee 90,20%, empathy 90,05%, and physical evidence 91,90%. Physical evidence (tangible) is servqual dimension occupied the first rank in terms of its’ influence on passenger satisfactions